Vehement Poetry: The Literary Sources of John Donne’s Ecclesiastical Via Media - Anne-Marie Miller-Blaise (XVII-XVIII, 2014)
This paper proposes to look at the unexpected forms of continuity between John Donne’s formal satires and elegies, written in his early years as a coterie poet, and his later definition of the Via Media of the Church of England. The young, provocative Donne was attracted to Roman poetry because of its potential for excess. When Donne entered holy orders, becoming one of the best advocates of the British middle way, he did not however turn abruptly away from these vehement literary forms of expression. Instead, they may well have provided him with some of his most efficient rhetorical and theological tools. The “oversexed,” hyperbolic language and the sceptical world of Roman satire and elegy paradoxically helped him shape a forceful understanding of the ecclesiastical mean, thought of in much more daring terms than a mere state of balanced in-betweenness.